ANALYZE ROLE OF THE ASCRIPTION OF RESPONSIBILITY ON THE CAUSATIVE FACTORS AND EFFORTS TO PREVENT STUNTING IN TODDLERS IN BALONGPANGGANG DISTRICT GRESIK - Eka Srirahayu Ariestiningsih; Dwi Faqihatus Syarifah Has; Guruh Kurniawan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The results of the Indonesian Basic Health Research noted that the prevalence of stunting in 2018 was 30.8%, 2019 as many as 27.67%. Because the procentage of stunting events in Indonesia ia still very high and the health problems of children and toddlers shuld be addressed. The aims of this research to analyze the Role of the Ascription of Responsibility on the causative factors and efforts to prevent stunting in toddlers, because it is based on the high cases of short and very short children in the working area of the Dapet PublicÂ  Health Center, Balongpanggang District, Gresik. There are 238 sample, consist of : 4 Posyandu Cadres, 2 health workers. 2 Lectures andÂ  230 toddler mother with stunting 115 sample and non stunting 115 sample. The statistical test used in this study was an exact fisher test with a significant rate of 5%.Role of parents variable is a significant variable, with sig 0,041 so it can be concluded that there is a significant and meaningful relationship or comparison between parent role variables and stunting, especially toddler mothers.On parent role variables, researchers analyzed the factors of the most comparison on parent role variables. Based on calculations using Kendal Tau test statistics, the following results were obtained.There arecomparationbetween exclusiveBreastfeedingand Breastfeeding Companion Food with stunting incidents in children aged 12-59 months Balongpanggang district Gresik.Provide education to pregnant women when visiting the Public Health Centre Balong Panggang and Polindes in order to consume PMT that has been given. Provide education to women, about nutrition in order to prepare nutrition during pregnancy well so as not to occur deficiency carbo during pregnancy.